PENTINGNYA LITERASI MEDIA DALAM MENGHADAPI INFORMASI HOAKS - Jily Fera Rensiyana; Khairuddin Khairuddin; Irfan Agil (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
The advancement of digital technology has facilitated access to information but also increased the spread of hoaxes, which can harm individuals and society at large. In this context, media literacy is an essential competency that people must possess to navigate the rapid and often inaccurate flow of information. Media literacy refers to the ability to access, comprehend, evaluate, and produce information critically and responsibly. This article highlights the importance of media literacy as a tool to curb the spread of hoaxes and foster a critically thinking society. It also discusses various strategies to enhance media literacy, including education, training, and the use of information verification technologies. By strengthening media literacy, society is expected to engage more actively and responsibly in the digital sphere.